Investigating the consequences of climate change under different land‐use regimes: a novel experimental infrastructure. Issue 3 (12th March 2019) - Schädler, Martin; Buscot, Francois; Klotz, Stefan; Reitz, Thomas; Durka, Walter; Bumberger, Jan; Merbach, Ines; Michalski, Stefan G.; Kirsch, Konrad; Remmler, Paul; Schulz, Elke; Auge, Harald
Abstract: Climate change and land‐use change are considered as the most important threats to ecosystems. Both factors can be expected to have interacting influences on ecosystem functions directly and indirectly via changes in biodiversity. Knowledge about these interactions is limited due to a lack of experiments which investigate climate change effects under different land‐use scenarios. Among the processes involved in ecosystem responses to global change, in particular, those occurring in soils or related to biotic interactions and microevolution were underinvestigated in previous experiments. Examinations of these relationships require spatial and temporal scales which go beyond those realized in the majority of ecological field experiments. We introduce a new research facility, the Global Change Experimental Facility (GCEF), which was designed to investigate the consequences of a future climate scenario for ecosystem functioning in different land‐use types on large field plots (400 m 2 ). Climate manipulation is based on projections for the period of 2070–2100 with an increased temperature and a changed precipitation pattern consisting of reduced precipitation in summer and increased precipitation in spring and autumn. We subject five different land‐use types (two farming systems, three grasslands), differing in land‐use intensity, to ambient and future climatic conditions. The use of automated roofs and side panels to passively increase night temperatures results in an average increase in daily mean temperature by 0.55°C accompanied by a stronger increase in minimum temperatures (up to 1.14°C in average) with longer frost‐free periods and an increase in growing degree days by 5.2%. The combined use of mobile roofs and irrigation systems allows the reduction (in summer by ~20%) and increase in rainfall (in spring and autumn by ~10%) according to future scenarios superimposed on the ambient variation in precipitation. The large plot size and the technical configuration allow the establishment of realistic land‐use scenarios and long‐term observations of responses of ecosystem functions and community dynamics on relevant temporal and spatial scales. Thus, the GCEF provides a well‐suited platform for the interdisciplinary research on the consequences of climate change under different land‐use scenarios.